Effect of the anther‐smut fungus Microbotryum on the juvenile growth of its host Silene latifolia. Issue 6 (11th July 2018) - Antonovics, Janis; Abbate, Jessica L.; Bruns, Emily L.; Fields, Peter D.; Forrester, Nicole J.; Gilbert, Kimberly J.; Hood, Michael E.; Park, Timothy; Taylor, Douglas R.
Abstract : Premise of the Study: Plant pathogens that form persistent systemic infections within plants have the potential to affect multiple plant life history traits, yet we tend to focus only on visible symptoms. Anther smut of Silene latifolia caused by the fungus Microbotryum lychnidis‐dioicae induces the anthers of its host to support fungal spore production instead of pollen, and the pathogen is primarily transmitted among flowering plants by pollinators. Nevertheless, most of its life cycle is spent in the asymptomatic vegetative phase, and spores falling on seedlings or nonflowering plants can also infect the host. The purpose of this study was to ask whether the fungus also had an effect on its host plant in the juvenile vegetative phase before flowering as this is important for the disease dynamics in species where infection of seedlings is commonplace. Methods: Leaf length and leaf number of inoculated and uninoculated juvenile plants were compared in greenhouse experiments, and in one experiment, disease status of the plants at flowering was determined. Key Results: Inoculated plants had shorter but more leaves, and reduced root mass at the early juvenile (preflowering) stage. Some of these effects were detectable in plants that were inoculated but showed no disease symptoms at flowering. Conclusions: These results show that pathogenic fungi can have endophyte‐like effects even in the total absence of their typical and more charismatic symptoms, and conversely that the assessment of endophyte effects on the fitness of their hosts should include all stages of the host life cycle.